Transparent superhydrophobic/superhydrophilic TiO2-based coatings for self-cleaning and anti-fogging - Lai, Yuekun (2013)
A stable titanate nanobelt (TNB) particle suspension was prepared by a hydrogen-bond-driven assembly of pre-hydrolysed fluoroalkylsilane (FAS) on its surface. A one-step electrophoretic deposition was applied to fabricate a transparent cross-aligned superhydrophobic TNB/FAS film on a conducting glass substrate. By controlling the deposition time, we have shown the transition between a “sticky” hydrophobic state (high contact angle with strong adhesion) and a “sliding” superhydrophobic state (high contact angle with weak adhesion). The optical transmittance can reach as high as 80% throughout most of the visible light region of the spectrum. These coatings have also displayed high chemical stability and self-cleaning ability. Upon heating the hydrophobic coatings at 500 °C, the TNB coating transforms into a porous TiO2(B) structure with superhydrophilic behavior and could be used for anti-fogging applications. With this TiO2-based system, we have demonstrated three different wetting states: superhydrophobicity with weak adhesion, high hydrophobicity with strong adhesion, and superhydrophilicity with immediate water spreading. Moreover, this work has also demonstrated superhydrophobic TNB/FAS films with high chemical stability and good self-cleaning performance and superhydrophilic pore-like TiO2(B) films with rapid water spreading and excellent anti-fogging ability.